Study of experimental signals during impacts and vibrations of robotic manipulator - Lima, Miguel F. M. (2007)
In practice the robotic manipulators present some degree of unwanted vibrations. In fact, the advent of lightweight arm manipulators, mainly in the aerospace industry, where weight is an important issue, leads to the problem of intense vibrations. On the other hand, robots intercting with environment often generate impacts that propagate through the mechanical structure and produce vibrations. Reference [1] mentions several techniques for reducing vibrations and its implementation either at the robot manufacturing stage or at the operational stage. One of the techniques, that has been receiving considerable attention, consists on the use of a micromanipulator [2], with a higher frequency response than the main manipulator, mounted at the end-effector and actively counter-acting the undesirable dynamics.